A second-order semidigital clock recovery circuit based on injection locking. - Hiok-Tiaq Ng (IEEE Journal of solid state circuits)
A compact (1 mm × 160 μm) and low-power (80-mW) 0.18-μm CMOS 3.125-Gb/s clock and data recovery circuit is described. The circuit utilizes injection locking to filter out high-frequency reference clock jitter and multiplying delay-locked loop duty-cycle distortions. The injection-locked slave oscillator output can have its output clocks interpolated by current steering the injecting clocks. A second-order clock and data recovery is introduced to perform the interpolation and is capable of tracking frequency offsets while exhibiting low phase wander.